Structure of Magnetospheric Current Systems and Mapping of High Latitude Magnetospheric Regions to the Ionosphere - Stepanova, M (Elsevier Ltd, 2018)
The structures of the main magnetospheric current systems are interesting to researchers because of their key role in magnetospheric physics, including the generation of geomagnetic storms and substorms. Ring current and tail current are usually considered as main sources of geomagnetic activity. We assume that the ring current is divided into the inner part located from ∼ 3 to ∼<7 RE and the outer part located from 7 RE to the magnetopause near noon and to ∼ 10–13 RE near midnight. We named the outer part of the ring current as the cut ring current (CRC). Due to compression of the geomagnetic field by the solar wind, the CRC is not concentrated near the equatorial plane at the noon sector, it spreads along field lines. We discuss the main properties of CRC and its role in the generation of field-aligned currents. We propose a method - based on the conservation of plasma pressure along a current line - that enables us to determine the position of the boundary between the ring and tail currents, and to determine the configuration of current lines which cross the magnetopause. At the same time, conservation of plasma pressure along a field line for plasmas in magnetostatic equilibrium enables us to analyze the auroral oval mapping into the equatorial plane regardless of any magnetic field model. It is well known that the auroral oval has a thick ring-like shape. We discuss that it is topologically impossible to map such a structure to a sheet band like structure in the tail. Our analysis showed that most of the auroral oval is mapped to the CRC region. We argue that including CRC as a part of the ring current allows to re-establish the traditional point of view, in which the ring current has a dominant role in Dst/SYM-H variations. © 2017 Elsevier Ltd